Cause and Effect of Quality Evaluation of Constructed School Buildings (Research Nepal Journal of Development Studies, 2023)
“Education is one thing no one can take away from you.” —Elin Nordegren. Such a wonderful precious assets are produced inside the school building. Thus the quality of school building is a causal infrastructure for future dimension of country. Thus the study is about the quality of school building. This study on quality evaluation of constructed school buildings, a case study of public schools of Siyari rural municipality of Rupandehi district, was be conducted during the period from July 2022 to June 2023. From the methodological perspective: Field observation, in-depth interview, focus group discussion and questionnaire survey were the tools for the field investigation. The proposed study was focused on finding out the quality of construction works within the territory of Siyari Rural Municipality of Nepal. The study finds out the level of the quality of the works. Furthermore, the study suggests the appropriate techniques for maintaining the quality of construction works.